Safety Assessment and Biological Effects of a New Cold Processed SilEmulsion for Dermatological Purpose. (5th November 2013) - Raposo, Sara; Salgado, Ana; Gonçalves, Lídia; Pinto, Pedro C.; Urbano, Manuela; Ribeiro, Helena M.
Abstract : It is of crucial importance to evaluate the safety profile of the ingredients used in dermatological emulsions. A suitable equilibrium between safety and efficacy is a pivotal concern before the marketing of a dermatological product. The aim was to assess the safety and biological effects of a new cold processed silicone-based emulsion (SilEmulsion). The hazard, exposure, and dose-response assessment were used to characterize the risk for each ingredient. EpiSkin assay and human repeat insult patch tests were performed to compare the theoretical safety assessment to in vitro and in vivo data. The efficacy of the SilEmulsion was studied using biophysical measurements in human volunteers during 21 days. According to the safety assessment of the ingredients, 1, 5-pentanediol was an ingredient of special concern since its margin of safety was below the threshold of 100 (36.53). EpiSkin assay showed that the tissue viability after the application of the SilEmulsion was 92 ± 6% and, thus considered nonirritant to the skin. The human studies confirmed that the SilEmulsion was not a skin irritant and did not induce any sensitization on the volunteers, being safe for human use. Moreover, biological effects demonstrated that the SilEmulsion increased both the skin hydration and skin surface lipids.